The Nativity story
It was the cruelest of time, under Herod's torturous reign, families struggles to survive and yet, in the midst of utter turmoil, a young woman's faith was put to the test. Join Mary and Joseph on an incredible journey of hope and discovery. Epic in its scope, yet intimate in its portrayal of this historical family